Impact of corporate social responsibility on firm performance: evidence from listed manufacturing firms of colombo stock exchange - Amali Hapuhinna, H.K.D.W.M.N. (University of Jaffna, 2019)
In general practice, businesses manipulate the changing competitive corporate environment and consumer’s trends with the complete focus of gaining high profits. Today, importance of Corporate Social Responsibility (CSR) cannot be neglected at any instance as it focuses on the integration of operations and actions by the businesses for the welfare of the society. This research study revolves around the investigation and analysis of the impact of the CSR on Firm Performance (FP) of the listed manufacturing firms in the Colombo Stock Exchange. The data were collected from 2010 to 2016 from the annual reports of the selected 36 companies. The researcher has used 6 proxies to measure CSR Earnings per Share, Leverage, Major Business Cost, Turnover of Payable, Proportion of Wages & Benefits and finally the Tax Pay Rate. By retaining the above six factors, the researcher studies the impact on FP under three dimensions; Return on Equity, Tobin Q and Return on Assets. Panel Data Regression method has been utilized for the analysis of the data and the results of the fitted Random Firm Effect Model reveals that EPS, Leverage, Major Business Cost, Turnover of Payable and the Tax Pay Rate have a statistically significant impact on the Return on Assets. According to the result of fitted Fixed Firm Effect Model, EPS is the only influential factor that positively impact on the Return on Equity while the Random Firm Effect Model for Tobin Q reveals that, none of the variables explain the variation in FP of the listed manufacturing companies.
Keywords: Corporate social responsibility; Return on equity; Tobin q ratio; Return on assets; Panel data analysis